A Comparative analysis of the academic performance of grade one pupils with and without preschool education : basis for enhanced pre-school activities - Singular, Cecille B. (Manila : National University, 2010)
This study aimed to show the importance of undergoing preschool education before entering grade one level of education. This is taking up for the people to be aware that preschool education is valuable in nurturing the child is early learning development. The researcher chose this problem because she believes this will be helpful for the teachers, parents, school administrator, students and community officials.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.